Determinants of Fraud Tendency among Accounting Students: The Moderating Role of Ethical Value - Shofiyah, Aniyatus; Ardini, Lilis (E-Jurnal Akuntansi, 2026)
This study analyzes factors influencing fraud tendency among accounting students based on the fraud hexagon theory, including pressure, opportunity, rationalization, competence, arrogance, and collusion, and examines ethical value as a moderating variable. Fraud tendency is considered an early indicator of unethical behavior, making its identification during education essential. This study applies a quantitative survey approach using questionnaires distributed to final-year accounting students at STIE Cendekia Bojonegoro and the Islamic University of Darul Ulum Lamongan. Data were analyzed using Moderated Regression Analysis (MRA). The results show that pressure, rationalization, and arrogance positively affect fraud tendency, while competence has a negative effect. Opportunity and collusion are insignificant. Ethical value negatively moderates the relationship between arrogance and fraud tendency but does not moderate the other factors. These findings highlight the importance of strengthening ethical values in accounting education to prevent fraud tendency early.